Synthesis and induction heating-induced self-healing of epoxy vitrimer nanocomposites - Huang, Jiahao; Zhang, Shixian; Wang, Qing; Zhu, Lei (Frontiers in Materials, 2025)
Epoxy vitrimers have attracted significant research attention due to their reprocessability, malleability, and potential self-healing capability. In this study, we successfully synthesized two vitrimers based on a bulky diepoxide monomer, 9,9-bis(4-glycidyloxyphenyl)fluorene (DGBPEF) and zinc catalysts. When DGBPEF reacted with flexible Pripol 1040, a soft vitrimer with a glass transition temperature (Tg) of 45 °C and a topology freezing transition temperature (Tv) of 207 °C was obtained. When DGBPEF reacted with glutaric anhydride, a hard vitrimer with a Tg of 166 °C and a Tv of 235 °C was obtained. While both samples exhibited good reprocessability upon hot-pressing around Tv, their surface scratches could not self-heal autonomously without applying pressure. Surface-functionalized superparamagnetic γ-Fe2O3 nanoparticles (∼20 nm) were dispersed into the soft vitrimer matrix to prepare nanocomposites. At a nanoparticle loading of 5 wt%, the application of an oscillating magnetic field induced rapid induction heating, raising the nanocomposite temperature to 240 °C–250 °C (well above the Tv) within 5–10 min, which enabled effective autonomous self-healing of surface scratches. In contrast, no self-healing was observed when the nanocomposite was directly heated in a vacuum oven at 240 °C. This difference is attributed to the possible migration of γ-Fe2O3 nanoparticles toward the crack site under an oscillating magnetic field, which enhances localized heating and triggers the autonomous self-healing response.